2020
DOI: 10.1002/etc.4806
|View full text |Cite
|
Sign up to set email alerts
|

A Generalized Bioavailability Model (gBAM) for Predicting Chronic Copper Toxicity to Freshwater Fish

Abstract: The generalized bioavailability model (gBAM) has been proposed as an alternative to the biotic ligand model (BLM) for modeling bioavailability and chronic toxicity of copper (Cu). The gBAM combines a log-linear effect of pH on free Cu 2+ ion toxicity with BLM-type parameters for describing the protective effects of major cations (calcium [Ca] 2+ , magnesium [Mg] 2+ , and sodium [Na] +). In the present study, a Windermere Humic Aqueous Model (WHAM) VII-based gBAM for fish was parametrized based on an existing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 35 publications
(109 reference statements)
0
13
0
Order By: Relevance
“…In the present study, we demonstrated the cross‐species application of the updated models to nonmodel cladocerans, rotifers, algae, and plants (Table 2). Recently, Nys et al (2020) proved that the updated chronic Cu fish bioavailability model developed based on juvenile rainbow trout ( O. mykiss ) can be extrapolated to other life stages of the same species as well of other fish species (i.e., P. promelas ). For a few taxonomic groups there remains some uncertainty related to the cross‐species applicability of the updated chronic Cu invertebrate bioavailability model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we demonstrated the cross‐species application of the updated models to nonmodel cladocerans, rotifers, algae, and plants (Table 2). Recently, Nys et al (2020) proved that the updated chronic Cu fish bioavailability model developed based on juvenile rainbow trout ( O. mykiss ) can be extrapolated to other life stages of the same species as well of other fish species (i.e., P. promelas ). For a few taxonomic groups there remains some uncertainty related to the cross‐species applicability of the updated chronic Cu invertebrate bioavailability model.…”
Section: Discussionmentioning
confidence: 99%
“…The updated models developed in this manuscript, together with the recently published chronic Cu fish bioavailability model (Nys et al, 2020), constitute a complete, consistent, and updated Cu bioavailability model set. It uses the most recent version of the WHAM VII, and all models are of the gBAM type, which has an improved estimation of the effect of pH on Cu toxicity compared with the classic BLM-type model (Nys et al, 2020;Van Regenmortel et al, 2015). The gBAM structure has the advantage that it avoids the need to consider the potential toxicity of CuOH and CuCO 3 , thereby reducing the number of model parameters without losing predictive power.…”
Section: Relevance Of the Updated Cu Bioavailability Model Set For Ri...mentioning
confidence: 99%
“…This complexity has been addressed by the development of BLM or alternatives such as the so‐called generalised bioavailability model (gBAM; e.g. Nys et al., 2020). The toxic effect depends on the metal speciation under different environmental conditions (spatial and temporal) and on the aquatic organism.…”
Section: Environmental Risk Assessmentmentioning
confidence: 99%
“…This complexity has been addressed by the development of BLM or alternatives such as the so-called generalised bioavailability model (gBAM; e.g. Nys et al, 2020).The toxic effect depends on the metal speciation under different environmental conditions (spatial and temporal) and on the aquatic organism. BLMs have been developed to predict acute and chronic toxicity to algae, invertebrates and fish for a range of physicochemical water parameters.…”
Section: Bioavailability Of Metal Compounds In the Water Phasementioning
confidence: 99%
“…In that regard, different bioavailability models such as biotic ligand models (BLMs) or generalized bioavailability models (gBAMs) have been developed over the years to account for differences in bioavailability and toxicity of metals in different water chemistries. Examples of this for fish are the chronic zinc (Zn; De Schamphelaere and Janssen 2004) and copper (Cu) BLM (Crémazy et al 2017) for Oncorhynchus mykiss and the recently published Cu gBAM for O. mykiss (Nys et al 2020). However, these bioavailability models were developed specifically to correct effect concentrations, obtained with concentration–effect models from individual‐level toxicity tests, measured after a certain test period.…”
Section: Introductionmentioning
confidence: 99%